2016
DOI: 10.18632/oncotarget.14126
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor BLU promotes TRAIL-induced apoptosis by downregulating NF-κB signaling in nasopharyngeal carcinoma

Abstract: A putative tumor suppressor BLU mapped on the chromosomal 3p21 region, is frequently lost in human tumors including nasopharyngeal carcinoma (NPC). To explore the underlying mechanism of tumor suppression by BLU, its potential to promote apoptosis induced by TRAIL, an effector molecule elaborated by natural killer-T (NKT) cells was investigated. BLU was re-expressed in NPC-derived HNE1 cells by recombinant adenoviral infection and the cells were challenged with recombinant TRAIL. The growth inhibition of BLU w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…USP19/ZMYND9 is a deubiquitinase, capable of stabilizing the KPC1 (Kip1 ubiquitylation-promoting complex 1) ligase for p27Kip1, c-IAP1, and inhibiting the degradation of an anti-apoptotic molecule cellular inhibitor of apoptosis (cIAP) [145]; while it has been reported that BLU/ZMYND10 which engages intracellular NF-κB pathway to downregulate its transcriptionally activated factor like cIAP2 [17]. USP19/ZMYND9 also interacts with HIF-1α and several components of the hypoxia pathway to inhibit their degradation in a deubiquitinase independent manner [146][147][148].…”
Section: Zmynd Proteins With Similar Structure But Variant Biological...mentioning
confidence: 99%
“…USP19/ZMYND9 is a deubiquitinase, capable of stabilizing the KPC1 (Kip1 ubiquitylation-promoting complex 1) ligase for p27Kip1, c-IAP1, and inhibiting the degradation of an anti-apoptotic molecule cellular inhibitor of apoptosis (cIAP) [145]; while it has been reported that BLU/ZMYND10 which engages intracellular NF-κB pathway to downregulate its transcriptionally activated factor like cIAP2 [17]. USP19/ZMYND9 also interacts with HIF-1α and several components of the hypoxia pathway to inhibit their degradation in a deubiquitinase independent manner [146][147][148].…”
Section: Zmynd Proteins With Similar Structure But Variant Biological...mentioning
confidence: 99%
“…One of the strategies that have been developed to use Ads in cancer therapy is to use replication-deficient adenoviral vectors to carry transgenes that codes for a tumor suppressor protein (p53) or proteins that induce apoptosis or cell cycle arrest ( 74 , 76 ). Wild-type p53 prevents development of cancer by inhibiting the activation of oncogenes and inducing programmed cell death (apoptosis) when the cell’s DNA repair functions are insufficient to repair DNA damage ( 77 ).…”
Section: Application Of Adenoviruses In Cancer Therapymentioning
confidence: 99%
“…In some studies, replication-deficient or replication-competent adenoviral vectors were used to deliver transgenes, which express a tumor suppressor protein or cytotoxic/suicide protein that induces cell cycle arrest or a death cascade [176,177]. More than 50% of cancers have a mutation in tumor suppressor gene p53.…”
Section: Cancer Immunotherapymentioning
confidence: 99%